Microslips as precursors of large slip events in the stick‐slip dynamics of sheared granular layers: A discrete element model analysis. Issue 16 (19th August 2013) - Ferdowsi, B.; Griffa, M.; Guyer, R. A.; Johnson, P. A.; Marone, C.; Carmeliet, J.
Abstract : [1] We investigate the stick‐slip behavior of a granular system confined and sheared by deformable solid blocks using three‐dimensional discrete element method simulations. Our modeling results show that large slip events are preceded by a sequence of small slip events—microslips—whose occurrence accelerates exponentially before the large slip event onset. Microslips exhibit energy release several orders of magnitude smaller than the large slip events. The microslip event rate is proposed as a measure of slip activity in the granular gouge layer. A statistical analysis shows that microslip event rate correlates well with large slip event onset and that variations in it can be used to predict large slip events. The emergence of microslips and their duration are found to be controlled by the value of the slipping contact ratio and are therefore related to the jamming/unjamming transition of frictional granular packings. Key Points: Microslip event rate is proposed as a measure of activity in granular layer Microslip event rate correlates well with large slip events Microslips emergence is controlled by the value of the slipping contact ratio